ASPEK HUKUM TELEMEDICINE DI INDONESIA - Bonsapia, Max; Jumiran (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Telemedicine has emerged as an innovative solution for healthcare services in Indonesia, especially amidst technological advancements and the need for equitable access to medical care. However, its implementation presents legal challenges concerning regulation, patient data privacy, and the professional liability of medical practitioners. This journal aims to analyze the legal aspects of telemedicine in Indonesia, focusing on the existing regulatory framework, compliance with ethical standards, and legal protection for medical personnel and patients. This research employs a normative juridical approach, examining laws and regulations such as Law Number 36 of 2009 concerning Health, Ministry of Health Regulation Number 20 of 2019 concerning Telemedicine Implementation, and related personal data protection regulations. Data was collected through a literature review of primary and secondary legal sources, including journals, articles, and official documents. The findings indicate that while Indonesia has a legal foundation for telemedicine, there are still regulatory gaps, particularly regarding technical operational standards, penalties for privacy violations, and cross-regional jurisdiction. Furthermore, patient data protection is often suboptimal due to weak legal implementation and a lack of awareness among telemedicine providers. This journal concludes that strengthening regulations, harmonizing inter-regulations, and providing legal education for healthcare professionals are crucial steps to support safe and legal telemedicine in Indonesia. Recommendations include developing more detailed technical guidelines and increasing penalties to ensure legal certainty.